Child Labor and School Achievement in Latin America - Gunnarsson, Victoria; Orazem, Peter F.; Sanchez, Mario A. (Published by Oxford University Press on behalf of the World Bank, 2014)
Child labors effect on academic achievement is estimated using unique data on third and fourth graders in nine Latin American countries. Cross country variation in truancy regulations provides an exogenous shift in the ages of children normally in these grades, providing exogenous variation in the opportunity cost of children's time. Least squares estimates suggest that child labor lowers test scores, but those estimates are biased toward zero. Corrected estimates are still negative and statistically significant. Children working 1 standard deviation above the mean have average scores that are 16 percent lower on mathematics examinations and 11 percent lower on language examinations, consistent with the estimates of the adverse impact of child labor on returns to schooling.